Influence of technology-assisted entrepreneurship learning on entrepreneurial mindset: Mediation analysis of attitude and self-efficacy - Pringgabayu, Dematria; Ramadhian, Mochamad Arief Rahman; Silvianita, Anita; Suryono, Herdiansyah Gustira Pramudia (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the influence of entrepreneurship education on students’ entrepreneurial mindset by examining the mediating roles of attitude and self-efficacy, with an emphasis on the integration of technology in private school settings. The entrepreneurial mindset is essential in fostering innovation, opportunity recognition, and adaptability in the digital economy. As private schools increasingly incorporate technology-enhanced learning such as virtual business simulations, digital collaboration tools, and online entrepreneurial modules, the role of technology in shaping students’ mindsets becomes increasingly relevant. This research uses a quantitative approach by distributing structured questionnaires to 350 high school students from selected private schools. Structural equation modeling (SEM) was used to examine the direct and indirect relationships among variables. The results show that entrepreneurship education, when supported by technology, significantly influences students’ entrepreneurial mindset. Additionally, attitude and self-efficacy serve as effective mediators in this relationship. The use of digital platforms fosters a more interactive and personalized learning environment, positively impacting students' confidence and interest in entrepreneurship. These findings suggest that integrating technology into entrepreneurship education enhances not only content delivery but also students’ psychological readiness for entrepreneurial action. The study contributes to the literature by highlighting the strategic role of educational technology in developing entrepreneurial potential in secondary-level private education.